Tinjauan Pengembangan Pemukiman dan Tantangan untuk Kota yang Berkelanjutan - Romiyadi Romiyadi; Fatmayati Fatmayati (Jurnal Sains dan Ilmu Terapan, 2025)
Rapid urbanization in Indonesia presents various environmental and social challenges, including increased disaster risk, urban heat island effects, and social disparities in urban settlements. This study examines the role of green infrastructure, sustainable spatial planning, and risk mitigation policies in addressing the adverse impacts of urban growth. Utilizing a literature review and spatial data analysis, findings indicate that implementing sustainable development strategies and integrating disaster risk data into urban planning can enhance urban resilience and improve the quality of life for city residents. The study emphasizes the importance of collaboration among government, communities, and stakeholders to achieve inclusive, environmentally friendly, and climate-adaptive urban development.